Imunomodulatory Effect of Red Tip Leaf’s (Syzygiummyrtifolium Walp.) Ethanol Extract on Male Rat - Sinulingga, Rony Andreas Harka; Hasibuan, Poppy Anjelisa Z; ., Yuandani; ., Rosidah; Dalimunthe, Aminah (Asian Journal of Pharmaceutical Research and Development, 2022)
The pattern of modern life demands that everything must be done very fast and instant. The quality of the consumed food, air pollution, lack of exercise and stress can cause the body’s endurance to decline continuously. The Red Tip (Syzigium myrtifolium Walp.) has been researched to have a flavonoid compound that has benefits as an anti-inflammatory and have potentially as an immunomodulator. The purpose of this study is to prove the effect of immunomodulator on the activity of phagocytosis, the total number and the differential of leukosit, the antibody titer value, and delayed type hypersensitivity response. Group treatment to test the clearance of carbon divided into 7 groups, each consisting of 5 male mice including the group of CMC-Na 0.5 %, Imboost ® dose 22.5 mg/ kgBB, the red tip leaf’s ethanol extract with dose of 50, 100, 200, 400, and 800 mg/kg orraly distributed for 7 days, and on the 8th day the carbon suspension was given using i.v. The blood intake were done in certain times and then the absorbance was measured using UV-Vis spectrophotometer. The liver and spleen of the rats were taken and weighed. The treatment group for antibody titer was divided into 7 groups with each consisting of 5 male mice using the same treatment as above except positive control that has been used levamisole on 25 mg/kgBB dose that has been distributed orraly for 14 days. The non spesific immune respond utilizing carbon cleanses method by measuring the carbon elemination speed and total amount and leukocyte differential. The specific immune response testing using antibody titers was done based on glutination which was formed and the delayed type hypersensitivity testing based on the mice swollen foot. The research outcome shows that the distribution of the red tip leaf’s ethanol extract with dose of 100, 200, 400, and 800 mg/kgBB is increasing the phagocytosis activity significantly compared to CMC-Na 0.5% (p < 0.05). The of the red tip leaf’s ethanol extract is increasing the total of leukocytes and neutrophils of the segment. The distribution of the red tip leaf’s ethanol extract with dose of 50, 100, 200, 400, and 800 mg/kgBB is increasing the formation of rat’s immune cell antibodies significantly compared to CMC-Na 0,5% (p < 0,05).This research prove that the red tip leaf’s ethanol extract has an effect of imunostimulator againts the phagocytosis activity, the total sum and leukocytes differential along with antibody titer value and the delayed type hypersensitivity.